(untitled) (Namibian Journal for Research, Science and Technology, 2022)
Decentralisation, in the Namibian public sector, was aimed at improving service delivery by regional and local authorities to the communities in Namibia. This research paper evaluates accountability of service delivery in the educational sector of the Directorate in Khomas Regional Council. This research paper used the qualitative approach and followed a triangulated method of data collection by using open and closed ended questions only. The findings of the research revealed that the understanding of the decentralisation policy and concepts are different among the participants. The paper recommends more sensitization, advocacy and training on the purpose and benefits of decentralization.